ANALISIS STRATEGI BAURAN PEMASARAN TERHADAP PENINGKATAN PELANGGAN PADA LEMBAGA RAFI BIMBEL TANGERANG - Fatma Setyaningsih (JMB : Jurnal Manajemen dan Bisnis, 2021)
This study aims to determine and analyze the effect of product, price, place, promotion, process, physical evidence and people one by one as well.  simultaneously to increase customers at the Rafi Bimbel Institute in Tangerang.  The research sample consisted of 85 parents of students whose children attended tutoring at the Rafi Bimbel Institute, Tangerang.  The data analysis technique used is multiple linear regression analysis, t test, F test and analysis of the coefficient of determination.  The research conducted resulted in the form of multiple linear regression equation Y = 3.032-0.134 X1 +0.007 X2 + 0.142 X3 + 0.338X4 + 0.458 X5 + 0.348 X6 + 0.181 X7 + e.  The t test produces a place and a process that has a significant effect on increasing customers at the Tangerang Rafi Bimbel Institute.  While the t test for price, promotion, product, people and physical evidence shows that there is no significant effect on increasing customers in Rafi Bimbel's Tutoring in Tangerang.  The F test produces product, price, place, promotion, process, physical evidence and people simultaneously have a significant effect on increasing customers in Rafi Bimbel's Tutoring in Tangerang.  Analysis of the coefficient of determination results in the influence of product, price, place, promotion, process, physical evidence and people simultaneously on the increase in customers at Rafi Bimbel's Tutoring in TangerangKeywords: Service Marketing Mix and Customer Improvement